Digital Divide in Children’s Short Stories of COVID-19 Pandemic in Banyumas, Indonesia - Aldi Aditya; Wiekandini Dyah Pandanwangi; Ummi Nurjamil Baiti Lapiana (Jurnal Lingua Idea, 2026)
This paper focuses on Sejuta Cerita Anak Banyumas an anthology of COVID-19-themed short stories, to explore how children responded to the pandemic amidst a significant regional digital divide. Employing a close reading method, the study examines 20 selected narratives as forms of life writing to understand the intersection of global crisis, youth agency, and technology. The research finds that children, acting as digital natives, integrated digital devices into their daily subjectivity, using them as vital emotional instruments to maintain resilience and generate creative novelty output to combat isolation and boredom. However, the analysis reveals that the pandemic was not a neutral event but one that exacerbated structural violence, exposing a complex continuum of digital inequality. This continuum categorizes youth into the "Haves," who possess the devices and literacy to remain productive; the "Marginalized," who face economic barriers to access; and the "Excluded," who suffer absolute digital silence due to a lack of basic infrastructure like electricity. The study concludes that because digital technology now fundamentally defines 21st-century childhood, inclusive policies such as government-sponsored computer loans and free village internet must persist beyond the pandemic to ensure equitable ICT diffusion and prevent the permanent marginalization of vulnerable youth.